DSS – DRONE based SIGNAL SYSTEM - Joshy, Joseph T; Devassy, Binet Rose; Krishnanunni M3,; Manjusha K V4, (International Journal of Psychosocial Rehabilitation, 2020)
The main issue after every Man-made and Natural disaster is the breaking of the communication system. This is a severe drawback to rescue operations. Three-fourth of the time spent on rescue operations is invested in finding people. People stuck in remote places are found after many days. Many people are dead by this time. These all happen due to the unavailability of the public communication system and a proper method to locate people after the disaster. Implementation of our system in such zones can save many human lives and make life-saving procedures spontaneous. An efficient solution for citizen safety is one of the best and needy things that are required during any disasters. Thus, we introduce a unique, stable, intuitive solution for this issue- DSS! It’s a system that provides GSM signal at the places of disaster, temporarily. It also helps to find the location of the people affected using mobile phone. Drone is deployed into the disaster zone where the communication is totally or partially damaged. It locates people. Signal repeaters are mounted on the drones that enable them to accept mobile signals from the nearby base stations and repeats them to the zone. Thus, people can use any cellular provider (with a nearby base station) in this repeated signal network. Using the signal provided by booster, a message is sent to the affected people's mobile number along with a link to download an app. The user now is able to install an app. Now we are able to locate them and their location is updated and displayed in the drone’s webpage. When the battery of drones is about to die, it will return to an origin point set by the user for replacement. Thus, the communication network is retained and people stuck in places can be found easily.